1988
DOI: 10.1521/jscp.1988.7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Beliefs, Belief Similarity, and Marital Distress: A Comparison of Models

Abstract: Although often examined separately, the joint influence of belief similarity and dysfunctionality on relationship satisfaction has not been investigated, and conceptual models to guide this inquiry are lacking. The present study compared five models of how similarity and irrationality may contribute individually and jointly to marital distress. Multiple measures of those constructs were administered to 49 nonclinical married couples. A content model received support when actual similarity was considered, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
3
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
0
18
3
2
Order By: Relevance
“…Contrary to the expectation that gendered patterns of socialization may lead men to develop more dysfunctional relationship beliefs, there was no gender difference in irrational beliefs related to the relationship. This finding was not consistent with previous research showing married women and men had different levels of irrational relationship beliefs (Bradbury & Fincham, 1993;Haferkamp, 1994;Jones & Stanton, 1988;Stackert & Bursik, 2003). As stated before, educational level had a significant effect on dysfunctional relationship beliefs.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Contrary to the expectation that gendered patterns of socialization may lead men to develop more dysfunctional relationship beliefs, there was no gender difference in irrational beliefs related to the relationship. This finding was not consistent with previous research showing married women and men had different levels of irrational relationship beliefs (Bradbury & Fincham, 1993;Haferkamp, 1994;Jones & Stanton, 1988;Stackert & Bursik, 2003). As stated before, educational level had a significant effect on dysfunctional relationship beliefs.…”
Section: Discussioncontrasting
confidence: 88%
“…In addition, some researchers have found that the low dyadic adjustment group had significantly more irrational relationship beliefs than did the high dyadic adjustment group (Debord et al, 1996;Möller & Van der Merwe, 1997;Möller & Van Zyl, 1991). Other researchers have reported similar findings for marital satisfaction (Jones & Stanton, 1988;Metts & Cupach, 1990;Stackert & Bursik, 2003;Sullivan & Schwebel, 1995). Moreover, some researchers have shown that there is gender difference in dysfunctional relationship beliefs.…”
mentioning
confidence: 87%
“…Thus, the interrelationship among perfectionism, sexual difficulties, and marital satisfaction for sexually dysfunctional men and their wives was examined. Given previous evidence in the literature that certain forms of dysfunctional cognitions (e.g., dysfunctional relationship beliefs) are associated with greater marital maladjustment (Eidelson and Epstein, 1982;Emmelkamp et al, 1987;Jones and Stanton, 1988), marital satisfaction scores were predicted to be inversely related to perfectionism scores in both men and women.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, in actual relationships, the effect of perceived similarity on satisfaction is stronger than the effect of actual similarity. Example studies that have shown that perceived similarity is more strongly associated than actual similarity with relationship quality in existing couples include Acitelli, Douvan, and Veroff (1993), Hendrick (1981), Jones and Stanton (1988), and Levinger and Breedlove (1966).The strong and consistent effects of perceived similarity on attraction (and satisfaction) may occur because both causal directions are operating. That is, not only is it likely that perceived similarity contributes to attraction (and satisfaction), but feelings of attraction and satisfaction may in turn lead to the perception of similarity.…”
mentioning
confidence: 99%
“…Therefore, in actual relationships, the effect of perceived similarity on satisfaction is stronger than the effect of actual similarity. Example studies that have shown that perceived similarity is more strongly associated than actual similarity with relationship quality in existing couples include Acitelli, Douvan, and Veroff (1993), Hendrick (1981), Jones and Stanton (1988), and Levinger and Breedlove (1966).…”
mentioning
confidence: 99%